2009
DOI: 10.1044/0161-1461(2009/08-0021)
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of University Professors Teaching Speech Sound Disorders: Nonspeech Oral Motor Exercises and Other Topics

Abstract: The instructors reported that they taught their students a variety of intervention techniques for children with SSD, although most did not teach the use of NSOMEs. These results contrast with previous research indicating that many speech-language pathologists use NSOMEs to improve children's speech (G.L. Lof & M.M. Watson, 2008).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our present findings indicate that SLPs use nonspeech oral motor exercises (NSOMEs) in the intervention process for all diagnostic groups, similar to what has been observed in other countries (Brumbaugh & Smit, 2013;Joffe & Pring, 2008;Rumbach et al, 2016;Ruscello, 2008;Watson & Lof, 2009). In their recent review, Lee and Gibbon (2015) concluded that there is no strong evidence that NSOMEs are an effective treatment or addition to the intervention of children with phonological speech disorder.…”
Section: Nonspeech Oral Motor Movementssupporting
confidence: 85%
“…Our present findings indicate that SLPs use nonspeech oral motor exercises (NSOMEs) in the intervention process for all diagnostic groups, similar to what has been observed in other countries (Brumbaugh & Smit, 2013;Joffe & Pring, 2008;Rumbach et al, 2016;Ruscello, 2008;Watson & Lof, 2009). In their recent review, Lee and Gibbon (2015) concluded that there is no strong evidence that NSOMEs are an effective treatment or addition to the intervention of children with phonological speech disorder.…”
Section: Nonspeech Oral Motor Movementssupporting
confidence: 85%
“…Given the ongoing debate regarding the precise role and efficacy of this approach (Mackenzie et al . , , Lof and Watson , Watson and Lof , Ziegler and Ackermann , Weismer ) it points to the importance of wider education and discussion (Maas ) in evidence based approaches in motor speech disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reasons given for using NSOMTs were (a) a high degree of exposure to NSOMT products and materials, (b) reports of prior clinical success with NSOMTs (either their own or reports from a colleague), and (c) beliefs that NSOMTs help in forming the foundation to acquire more complex movements required for speech, that speech develops from earlier occurring oral behaviors, and that NSOMTs help to build up strength needed to produce speech. In contrast, a survey of 91 university instructors found that 75% of them did not teach their students to use NSOMTs (Watson & Lof, 2009). Taken together, the results of these surveys highlight the differences of opinion that clinicians and clinical instructors/researchers can have about NSOMTs.…”
mentioning
confidence: 88%